Digital Transformation And Omnichannel Strategies In Indonesian Agricultural Retail: A Technology Organization Environment Perspective - Kawet, Raymond Christian; Raintung, Michael Ch.; Mandey, Silvya Lefina; Soegoto , Agus Supandi; Paat , Franda Benedicta; Rondonuwu, Christy Natalia (Sam Ratulangi University, 2026)
Digitalisation is reshaping how agricultural products and farm inputs move along value chains, yet the role of agricultural retailers in this process remains underexplored. This study investigates digital transformation and omnichannel strategies in Indonesian agricultural retail, focusing on agro input shops and agrifood outlets that combine physical stores with digital channels such as social media, marketplaces, and websites. Guided by the Technology Organization Environment framework, it analyses how technological, organisational, and environmental factors influence omnichannel adoption, identifies key barriers, and examines perceived effects on business performance. A mixed method design is employed: in the qualitative phase, semi structured interviews with owners and managers explore current digital practices, drivers, and obstacles and inform the development of a structured questionnaire; in the quantitative phase, survey data from agricultural retailers in several Indonesian regions are analysed using partial least squares structural equation modelling. The results indicate that all three Technology Organization Environment dimensions have positive and significant relationships with the degree of omnichannel adoption. The study also finds important barriers, including limited rural digital and logistics infrastructure, seasonal demand patterns, perceived high costs of integrated systems, gaps in digital skills and confidence, and difficulties in integrating data and processes across platforms. Higher levels of omnichannel adoption are associated with improved perceived sales, customer relationships, and operational efficiency. Overall, the findings suggest that well-designed omnichannel strategies can strengthen the intermediary role of agricultural retailers and support more efficient and inclusive agricultural marketing systems in Indonesia. Keywords: Digital transformation; Omnichannel retail; Agricultural retail; Agrifood sector; Technology Organization Environment (TOE); Indonesia